METHODS FOR STUDYING THE STRUCTURE AND MECHANICAL PROPERTIES OF REFRACTORY METALS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses macro and microstructural studies of initial workpieces, as well as semi-finished products for all technological schemes. In this case, samples for microstructural analysis were prepared according to the usual method. During the analysis of the microstructure, its uniformity of size and elongation of grains, texture, the presence of impurities, micropores and microcracks were assessed.